Structured vocabularies for proteins - Chang, Elizabeth; Dillon, Tharam S.; Sidhu, Amandeep (IFMBE - The International Federation for Medical and Biological Engineering, 2005)
In this paper we introduce various vocabularies and definitions used for defining Protein Ontology. Protein Ontology provides the technical and scientific infrastructure and knowledge to allow description and analysis of relationships between various proteins. Protein Ontology uses relevant protein data sources of information like PDB, SCOP, and OMIM. Protein Ontology describes: Protein Sequence and Structure Information, Protein Folding Process, Cellular Functions of Proteins, Molecular Bindings internal and external to Proteins, and Constraints affecting the Final Protein Conformation.